Terhadap kompetensi digital guru SMP Negeri di Kecamatan Ujung Batu Kabupaten Rokan Hulu pada masa pandemi covid-19 - Nurlaila, Lilik; Bastian, Adolf; Rahmat , Adi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Digital competence is very important in the context of education during the pandemic,especially for teachers to support the teaching and learning process. The purpose of thisstudy was to determine the effect of individual characteristics, organizational support anddigital media utilization patterns on the digital competence of SMPN teachers in UjungBatu District, Rokan Hulu Regency. This research is a survey research with 73respondents. Data was collected by using questionnaires and data analysis usingdescriptive statistics and SEM-PLS analysis. The results of the study indicate thatindividual characteristics have a significant effect on teacher digital competence, therewas a significant effect of organizational support on teacher digital competence and therewas a significant effect digital media utilization patterns on digital competence in UjungBatu sub-district, Rokan Hulu Regency.